Book Review Essay: “Psychoanalysis, Clinic and Context – Subjectivity, History and Autobiography” by Ian Parker - Néstor Braunstein (EJP import test, 2020)
Psychoanalysis, Clinic and Context – Subjectivity, History and Autobiography by Ian Parker London and New York, 2020, 208pp.